Ответы и объяснения

  • fuflunce
  • почетный грамотей
2013-01-06T19:12:13+04:00

2) \frac{n+\sqrt{n}-12}{3-\sqrt{n}} = \frac{(n+\sqrt{n}-12)*(3+\sqrt{n})}{(3-\sqrt{n})*(3+\sqrt{n})} =\\ = \frac{3n+n\sqrt{n}+3\sqrt{n}+n-36-12\sqrt{n}}{9-n}=\\ =\frac{4(n-9)+\sqrt{n}(n-9)}{9-n}=\frac{(n-9)(4+\sqrt{n})}{9-n} = -4-\sqrt{n}

 

1) x^2 - 2(m+a)x +4ma

D/4 = (m+a)^2 - 4ma = m^2 + 2ma + a^2 - 4ma = (m-a)^2

x = (m+a) +- (m-a) 

x1 = m + a + m -a = 2m

x2 = m + a - m + a = 2a

x^2 - 2(m+a)x +4ma = (x - 2m)(x - 2a)

 

x^2 + 2(a+b)x +4ab

D/4 = (a+b)^2 - 4ab = (a-b)^2

x12 = -(a+b) +- (a-b)

x1 = -a-b+a-b = -2b

x2 = -a-b-a+b = -2a

x^2 + 2(a+b)x +4ab = (x+2a)(x+2b)

 

\frac{(x-2m)(x-2a)(x-2b)(x+2b)(x+2a)^2}{(x+2a)(x+2b)(x-2a)(x+2a)(x-2m)}=\\ =(x-2b)(x+2a)